Новые виды клещей семейства Scutacaridae (Trombidiformes) - Севастьянов, В.Д. (Вестник зоологии, 1974)
Soils of the Ukraine are inhabited by Heterodispus cerealis sp. n., Imparipes platycephalus sp. n. and I. puberulus sp. n. and I. carabidophilus sp. n. lives on the soil. inhabiting tiger and ground beetles. I. cavernophilus sp. n. dwells in caves of Azerbaijan, I. posietis sp. n. was found in oak stump in the South Primorie.